Validity of Physics Teaching Materials Based on STEM to Improve Climate Literacy of High School Students - Octaviani Mutmainah; Abdul Hakim; Muliati Syam (Department of Physics Education, Universitas Mataram, 2022)
This study aimed to develop physics teaching material based on Science, Technology, Engineering, and Mathematics (STEM), which criteria valid. The study employed is development research using the ADDIE development model. The ADDIE which consists of five stages, namely Analyze, Design, Development, Implementation, and Evaluation which is limited to three stages, namely; (1) analysis, (2) design, and (3) development for aspects of validity. The validity of the teaching material was determined with the aid of experts and learning practitioners. The validation results of physics teaching material based on STEM were categorized as very valid with a validity level of 92% and student response with a score of 85%. Based on the results obtained, the climate change physics teaching materials based on STEM are suitable for improving high school students' climate literacy.